The timing of continuous renal replacement therapy initiation in sepsis-associated acute kidney injury in the intensive care unit: the CRTSAKI Study (Continuous RRT Timing in Sepsis-associated AKI in ICU): study protocol for a multicentre, randomised controlled trial. Issue 2 (19th February 2021) - Chen, Wei-yan; Cai, Li-hua; Zhang, Zhen-hui; Tao, Li-li; Wen, Yi-chao; Li, Zhi-bo; Li, Li; Ling, Yun; Li, Jian-wei; Xing, Rui; Liu, Xue-yan; Lin, Zhuan-di; et al.
Abstract : Introduction: Acute kidney injury (AKI) is one of the most common organ dysfunction in sepsis, and increases the risk of unfavourable outcomes. Renal replacement therapy (RRT) is the predominant treatment for sepsis-associated AKI (SAKI). However, to date, no prospective randomised study has adequately addressed whether initiating RRT earlier will attenuate renal injury and improve the outcome of sepsis. The objective of the trial is to compare the early strategy with delayed strategy on the outcomes in patients with SAKI in the intensive care unit (ICU). Methods and analysis: This is a large-scale, multicentre, randomised controlled trial about SAKI. In total, 460 patients with sepsis and evidence of AKI stage 2 of Kidney Disease Improving Global Outcomes (KDIGO) will be recruited and equally randomised into the early group and the delay group in a ratio of 1:1. In the early group, continuous RRT (CRRT) will be started immediately after randomisation. In the delay group, CRRT will initiated if at least one of the following criteria was met: stage 3 of KDIGO, severe hyperkalaemia, pulmonary oedema, blood urea nitrogen level higher than 112 mg/dL after randomisation. The primary outcome is overall survival in a 90-day follow-up period (90-day all-cause mortality). Other end points include 28-day, 60-day and 1-year mortality, recovery rate of renal function by day 28 and day 90, ICU and hospital length of stay, the numbers of CRRT-free days, mechanical ventilation-free days and vasopressor-free days, the rate of complications potentially related to CRRT, CRRT-related cost, and concentrations of inflammatory mediators in serum. Ethics and dissemination: The trial has been approved by the Clinical Research and Application Institutional Review Board of the Second Affiliated Hospital of Guangzhou Medical University (2017–31-ks-01). Participants will be screened and enrolled from patients in the ICU with SAKI by clinicians, with no public advertisement for recruitment. Results will be disseminated in research journals and through conference presentations. Trial registration: NCT03175328 .